2018
DOI: 10.1016/j.jor.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A higher altitude is an independent risk factor for venous thromboembolisms following total shoulder arthroplasty

Abstract: Introduction: High altitudes lead to physiological changes that may predispose to venous thromboembolisms (VTE) including deep vein thrombosis (DVT) and pulmonary embolism (PE). No prior study has evaluated if there is also a higher risk of VTEs after total shoulder arthroplasties (TSAs) performed at higher elevations compared to lower elevations. The purpose of this study was to identify if undergoing TSA at a higher altitude center (> 4000 feet above sea level) is an independent risk factor for a postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Although we analyzed patient demographic characteristics, comorbidities, and complications associated with VTE, many risk factors found in prior studies were not found to be risk factors for VTE in our study. For example, inpatient status, sex, anesthesia type, obesity, smoking, malignancy, operative time, CHF, COPD, anemia, and independent functional status were not associated with VTE occurrence as loosely suggested in previous literature 12, 14, 15, 33, 36, 38. However, even in recent studies, these risk factors and pre-existing conditions have not been replicated, with statistical significance often not having been met 21, 40.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although we analyzed patient demographic characteristics, comorbidities, and complications associated with VTE, many risk factors found in prior studies were not found to be risk factors for VTE in our study. For example, inpatient status, sex, anesthesia type, obesity, smoking, malignancy, operative time, CHF, COPD, anemia, and independent functional status were not associated with VTE occurrence as loosely suggested in previous literature 12, 14, 15, 33, 36, 38. However, even in recent studies, these risk factors and pre-existing conditions have not been replicated, with statistical significance often not having been met 21, 40.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies have suggested that patients with comorbidities including prior VTE, advanced age, critical care hospitalization, diabetes, heart disease, malignancy, lung disease, renal disease, obesity, pregnancy, and blood disorders are thought to have an increased risk of VTE 12, 15, 33. In addition, modifiable factors such as mobility, smoking, prolonged operative time, patient positioning, intramedullary instrumentation, and alcohol use have been implicated in the increased risk of VTE in TSA patients 12, 14, 33, 42.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While this may under report actual VTE rates, theoretically these errors would occur at equal rates in both cohorts studied. It is also possible that our elevation parameters, which we based on prior non-spinerelated studies, 7,8,27 may not adequately identify if altitude was a risk factor for this cohort and other elevations would instead show a risk. Additionally, there is an inability to screen patients preoperatively based on our methods, and so preexisting DVTs or PEs may not have been excluded.…”
Section: Limitationsmentioning
confidence: 99%
“…Within the field of orthopaedic surgery, several studies have found an increased incidence rate of VTEs with higher altitude following arthroscopic knee surgery as well as total joint replacements. 11,12 However, there is minimal data investigating the effect that altitude plays on the development of VTEs in pelvic ring and acetabular fractures.…”
Section: Introductionmentioning
confidence: 99%